Improving a convection‐permitting model simulation of a cold air outbreak. (17th April 2013) - Field, P. R.; Cotton, R. J.; McBeath, K.; Lock, A. P.; Webster, S.; Allan, R. P.
Abstract A convection‐permitting local‐area model was used to simulate a cold air outbreak crossing from the Norwegian Sea into the Atlantic Ocean near Scotland. A control model run based on an operational configuration of the Met Office UKV high‐resolution (1.5 km grid spacing) NWP model was compared to satellite, aircraft and radar data. While the control model captured the large‐scale features of the synoptic situation, it was not able to reproduce the shallow (<1.5 km) stratiform layer to the north of the open cellular convection. Liquid water paths were found to be too low in both the stratiform and convective cloud regions. Sensitivity analyses including a modified boundary‐layer diagnosis to generate a more well‐mixed boundary layer and inhibition of ice formation to lower temperatures improved cloud morphology and comparisons with observational data.